Research Progress on Specific Recognition and Interaction Mechanism between Antibody and Antigen in Immunoassay for Heavy Metal Residues - HUANG Junjun, ZHOU Mengxin, LÜ Xiaodan, XIAO Zhili (Shipin Kexue)
Heavy metals are highly toxic and can contaminate a wide range of foods. Their pollution and residues can bring about serious harm to food safety. Therefore, it is critical to strengthen efforts to detect heavy metal residues in food products. Immunoassay is promising for the rapid and efficient detection of heavy metals. Heavy metal antibodies are at the heart of immunoassays for the detection of heavy metals. Heavy metal antigens consist of two parts: heavy metal ions and chelating agents. Due to the structural similarity among metal ions and the universality of chelating agents, the resulting antibodies often show inadequate specificity, although antibodies with good specificity have been reported in some literatures. Therefore, it is significant to explore the specific recognition and interaction mechanism between heavy metal antibodies and antigens. In this article, we elaborate three research methods for understanding the recognition mechanism between heavy metal antibodies and antigens and recent progress in this area, and analyze the critical factors for the specific recognition and interaction. We hope that this review will provide a reference for enhancing the performance of heavy metal antibodies, and lay the foundation for establishing efficient, sensitive and specific methods for the detection of heavy metal residues in foods.